Varying importance of cuticular hydrocarbons and iridoids in the species-specific mate recognition pheromones of three closely related Leptopilina species - Weiss, Ingmar; Hofferberth, John; Ruther, Joachim; Stökl, Johannes (Frontiers in Ecology and Evolution, 2015)
Finding a suitable mate for reproduction is one of the most important tasks for almost all animals. In insects this task is often facilitated by pheromone-mediated communication. While insect pheromones in general show enormous chemical diversity, closely related species often use structurally similar compounds in their pheromones. Despite this similarity, pheromones of congeneric species living in sympatry need to be species specific. We investigated the pheromone-mediated mate recognition by males of three closely related species of Leptopilina, a genus of parasitoid wasps that utilize the larvae of Drosophila as hosts. The study species, L. heterotoma, L. boulardi, and L. victoriae, occur sympatrically and have a similar ecology and life history. We have found that mate recognition is species specific in all three species. This species specificity is achieved by a differing importance of cuticular hydrocarbons (CHCs) and iridoids in the female mate recognition pheromones. In L. heterotoma the iridoids are of major importance while CHCs play a negligible role. In L. boulardi, however, the CHCs are as important as the iridoids, while in L. victoriae, the CHCs alone elicit a full behavioral response of males. Our results provide novel insights into pheromone evolution in insects by showing that selection on two completely different classes of chemical compounds may generate conditions where compounds from both classes contribute to a varying degree to the chemical communication of closely related species and that this variation also generates the species specificity of the signals.